Peran Pustakawan dalam Pemenuhan Kebutuhan Informasi Pemustaka di Perpustakaan UNAND - Afrizal, Naura Salsabila; Marlini, Marlini; Desriyeni, Desriyeni (Lembaga Yasin AlSys, 2026)
This study discusses the role of librarians in meeting users’ information needs at the Andalas University Library, emphasizing the importance of librarians as intermediaries between information resources and users amid the rapid development of information technology. The aim of the study is to analyze how librarians perform this function within the context of a modern academic library. The method employed is a literature study by reviewing various written sources related to the role of librarians, information services, and the development of digital libraries in academic settings. The findings indicate that librarians no longer function solely as collection managers, but also as learning facilitators and research partners who actively support the academic activities of the university community. Strategies to improve the quality of information services are carried out through the development of digital library systems, the enhancement of librarians’ professional competencies, and the optimization of facilities and collections so that they are more responsive to users’ needs. The study concludes that digital transformation is key to creating information services that are efficient, accurate, and relevant to users’ academic needs, while also underscoring the need to strengthen librarians’ capacities to ensure the continuity of the library’s strategic role in higher education institutions.